Relationship between pedagogical support and reading comprehension in teachers of the Local Educational Management Unit of Piura - Ramos Vílchez, Elsa (2025)
This study analyzes the correlation between pedagogical support and reading comprehension in teachers at the UGEL of Piura. The objective was to see how teaching support affects teachers' reading comprehension skills. The research is basic, quantitative, with a non-experimental correlational design. To do so, two questionnaires were tested on 50 primary school teachers chosen by purposive sampling; these teachers participate extensively in educational support measures. The results demonstrate that consistent, well-structured support greatly improves reading skills, including literal, inferential, and critical comprehension. Furthermore, it is concluded that frequent and good help increases connection and sense of ability among teachers about their skills, helping to increase teaching and learning in students.